A spatial and nonstationary model for the frequency of extreme rainfall events. Issue 1 (11th January 2013) - Gregersen, Ida Bülow; Madsen, Henrik; Rosbjerg, Dan; Arnbjerg‐Nielsen, Karsten
Key Points A model of spatial and temporal changes in the frequency of extreme rainfall Explanatory variables in two dimensions and correlation among the observations Trend in frequency is correlated to changes in summer rainfall and temperature